Geometry [ includes plane, analytic, and transformational geometries - Rich, Barnett , 1906-; Thomas, Christopher , 1973- (Schaum's outlines, 2009)
665 fully solved problems; concise explanations of all geometry concepts; covers solid geometry and transformation.